Diagnosis and troubleshooting of automotive electrical, electronic, and computer systems - Halderman, James D. 1943- (Prentice Hall, 1997)
Comprehensive yet easy-to-read, this book includes both automotive electrical as well as engine performance topics all in one book. It is NATEF- and ASE-correlated and presents principles and practices of diagnosis and troubleshooting of automotive electrical, electronic, and computer systems in a clear, concise format and at a level of detail that far exceeds most similar texts.